2016
DOI: 10.3390/ijms17050696
|View full text |Cite
|
Sign up to set email alerts
|

Identification of More Feasible MicroRNA–mRNA Interactions within Multiple Cancers Using Principal Component Analysis Based Unsupervised Feature Extraction

Abstract: MicroRNA(miRNA)–mRNA interactions are important for understanding many biological processes, including development, differentiation and disease progression, but their identification is highly context-dependent. When computationally derived from sequence information alone, the identification should be verified by integrated analyses of mRNA and miRNA expression. The drawback of this strategy is the vast number of identified interactions, which prevents an experimental or detailed investigation of each pair. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Although Luding et al [26] explicitly considered significant negative correlation between miRNA and mRNA, since our methodology was originally designed so as to be applied to unmatched data set [8], we did not require the significant negative correlations between miRNA-mRNA pairs explicitly. Although we required reciprocal differential expression, this did not always guarantee negative correlation, since samples are unbalanced between normal kidney and Wilms tumors (the number of Wilms tumor samples are much more than normal kidney); if there are no negative correlations within Wilms tumor samples, there may not be significant negative correlation between miRNA and mRNA.…”
Section: Significant Negative Correlation Between Mirna-mrna Pairsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although Luding et al [26] explicitly considered significant negative correlation between miRNA and mRNA, since our methodology was originally designed so as to be applied to unmatched data set [8], we did not require the significant negative correlations between miRNA-mRNA pairs explicitly. Although we required reciprocal differential expression, this did not always guarantee negative correlation, since samples are unbalanced between normal kidney and Wilms tumors (the number of Wilms tumor samples are much more than normal kidney); if there are no negative correlations within Wilms tumor samples, there may not be significant negative correlation between miRNA and mRNA.…”
Section: Significant Negative Correlation Between Mirna-mrna Pairsmentioning
confidence: 99%
“…In the previous study [8], the recently proposed principal component analysis (PCA) based unsupervised feature extraction (FE) was successfully applied to miRNA-mRNA interaction identification in various cancers. It worked pretty well although it was not modified from samples to samples (from cohorts to cohorts) so as to get feasible results, but employed single common criterion to identify feasible miRNA-mRNA pairs.…”
Section: Introductionmentioning
confidence: 99%
“…The various unsupervised gene selection methods were invented, e.g., highly variable genes, bimodal genes and dpFeature and principal component analysis (PCA) based unsupervised feature extraction (FE) (50, 34, 49, 42, 25, 31, 27, 40, 47, 4, 5, 44, 45, 13, 12, 11, 51, 39, 43, 22, 23, 24, 26, 41, 48). Chen et al (2) recently compared genes selected by these methods and concluded that the genes selected are very diverse and have their own (unique) biological features.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, I propose a strategy that can infer drug candidates from drug treatmentassociated gene expression profiles without the information about known compounds for diseases. In this strategy, I employ the tensor decomposition (TD)-based unsupervised feature extraction (FE) approach, which is an extension of the recently proposed principal component analysis (PCA)-based unsupervised FE; PCA-based unsupervised FE successfully solved various bioinformatic problems [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. In this TD-based strategy, tensors were generated using a mathematical product of a gene expression profile of drug-treated cell lines and of a gene expression profile of a disease.…”
Section: Introductionmentioning
confidence: 99%